Narrativas autobiográficas do percurso formativo de egressos da Licenciatura em Matemática da UFMS/CPTL - GERSON DOS SANTOS FARIAS (2022)
This study is linked to the Postgraduate Program in Mathematics Education, Master's level, of the Mathematics Institute (INMA) of the Federal University of Mato Grosso do Sul (UFMS), along the research line "Teacher Education and Curriculum" and linked to the Research Group Formation and Mathematics Education (FORMEM). The research aimed at understanding the formative processes of teachers who graduated from the Mathematics Teaching Degree Course at UFMS/Campus of Três Lagoas (CPTL), during the process of becoming a Mathematics teacher, as well as to know the profile of the graduates and investigate their personal and professional trajectories. The study aimed to answer the following research question: How is the formative journey of teachers who graduated from the Mathematics Undergraduate Program at UFMS/CPTL? In order to do so, we adopted a theoretical framework that contemplates the discussion about the historical and social aspects that permeate the formation of teachers in Brazil and, in the middle of this movement, we also tried to dialogue with the specificities that are part of the formation and performance of Mathematics teachers. As methodological references, we used the (auto)biographical research approach, subsidized by the production of autobiographical narratives. Facing the pandemic context of COVID-19, the data of this research were produced with 6 (six) egress teachers, inspired by the technique of autobiographical narrative interviews, based on Schütze (2013), and analyzed under the perspective of metaphorical reading in three times: Time I: Pre-analysis / cross-reading; Time II: Thematic reading - thematic units of analysis and Time III: Interpretive-comprehensive reading of the corpus, called by Souza (2006; 2014) as comprehensive-interpretive analysis. In this research, Time I was configured as the moment of reading the autobiographical narrative interviews of each egress teacher, in order to build the autobiographical profile of the group. Then, in Time II, the thematic analysis was performed, from the singularities and individual and collective particularities of each story, thus, the thematic units of analysis emerged from the speeches, as follows: formative continuum; theory and practice; mathematics, contexts and scenes; early career; professional identity; university and school relationship; the pandemic context and the teaching work. Finally, in Time III, we propose a (re)grouping of the regularities and non-regularities present in each autobiographical narrative. The results show the plurality of narrated experiences, which imprint significant marks and show the singularity and subjectivity of each individual. In highlighting the pandemic period, the teachers' statements point to the complexity of acting in front of a context in which they were not prepared. Therefore, they faced (and continue to face) challenges related to the teaching of mathematics and teacher training; to the precariousness and devaluation of the teaching work in Brazil; to social inequalities reflected in the conditions of access to education in the remote modality; as well as weaknesses regarding school organization and management. The study also points out the need for reflection on the formative journey of teachers, as a way to create spaces for dialogue, since reflection engenders a power of transformation of reality in the subject that narrates.